Comparative analysis of phasic left atrial strain and left ventricular posterolateral strain to discriminate Fabry cardiomyopathy from other forms of left ventricular hypertrophy. (14th October 2021) - Frumkin, D; Knebel, F; Stangl, K; Mattig, I; Laule, N; Canaan-Kuehl, S; Brand, A
Abstract: Background: "Classic" echocardiographic signs of Fabry cardiomyopathy (FC), such as left ventricular hypertrophy (LVH) and posterolateral strain deficiency (PLSD) have a low diagnostic accuracy in clinical practice. Purpose: Our aim was to evaluate the diagnostic accuracy of phasic left atrial strain impairment compared to PLSD to discriminate FC from other forms of LVH. Methods: 40 patients with LVH due to bioptically and genetically confirmed FC or with LVH due to other causes, defined by exclusion of storage diseases, such as Amyloidosis or FC, by myocardial biopsy, were retrospectively analysed. Standard echocardiographic views (Vivid E9, GE, Vingmed, Horton) were used to analyse left atrial (LA) reservoir, conduit, and contraction strain using 2D speckle tracking echocardiography (2DSTE; EchoPAC software, GE) as well as the PLSD, obtained by the mean of deformation values in basal posterior and lateral segments in a 17-segment model. Receiver operating characteristic (ROC) curve analysis and a logistic regression model were performed to assess the diagnostic accuracy of LA and LV strain impairment. Results: FC was confirmed in 20 patients by genetic testing and myocardial biopsy. In the LVH group, 12 patients were classified to have hypertrophic cardiomyopathy, two had hypertensive heart disease, and six expressed the pattern of LV hypertrophy combined with borderline myocarditis. LV septum thickness (15.8mm±3.4 in FC; 17.9mm±4.3 in LVH) and left atrial volume index (LAVI) (36.7ml/m 2 ±11.3 in FC; 45.7ml/m 2 ±16.3 in LVH) as well as LVEF (54.2%± 9.8 in FC; 52.5%±7.7 in LVH, ) were not statistically different between groups. LV filling parameters such as E/A (1.2±0.5 in FC; 1.2±0.7 in LVH) and E/e' (11.0±4.9 in FC; 13.2±5.3 in LVH) showed a slightly more advanced impairment in the LVH group. Global and regional LV function was not different between groups (LVGLS −13.8±3.7% in FC and −12.8±3.7% in LVH; PLSD −10.7±5.2% in FC and −8.85±3.9% in LVH; p-value?). LA reservoir strain (LASr) and LA conduit strain (LAScd) were significantly impaired in FC compared to the LVH group (LASr 14, 6±2.5% in FC and 26.3±8.5% in LVH, p<0.01; LAScd −5.9±2.6% in FC and −15.8±4.7% in LVH, p<0.01). In ROC analysis, LASr, with an area under the curve (AUC) of 0.81 (95% CI 0.64–0.97) and LAScd with an AUC of 0.85 (95% CI 0.71–0.99), respectively, showed the highest diagnostic accuracy to discriminate FC. PLSD, in contrast, held a low diagnostic accuracy with an AUC of only 0.47 (95% CI 0.27–0.68). Conclusion: A substantially higher diagnostic accuracy could be shown for LASr and LAScd impairment in discriminating FD and other forms of LVH compared to PLSD. The echocardiographic assessment of phasic LA strain may help to identify FC in patients with unclear LVH. Funding Acknowledgement: Type of funding sources: None.